2006
DOI: 10.1227/01.neu.0000210224.54816.40
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of the Filum Terminale and Its Elastic Fibers

Abstract: The longitudinal arrangement of collagen bundles and the impressive amount of elastic and elaunin fibers should elicit considerable elastic properties to the FT. An altered elasticity mechanism has been proposed for TCS; further studies are needed with TCS patients to define whether the collagen structure, Type 1/Type 3 proportion, or elastic fiber content are altered, which could lead to new histopathological definitions of TCS, helping neurosurgeons in the difficult management of TCS patients with normal lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 26 publications
2
37
2
Order By: Relevance
“…Various studies have demonstrated abundance of collagen and elastic fibres, as well as undifferentiated, progenitor cells or multipotent precursors, explaining, according to some authors, the occurrence of ependymal tumours or teratoma at that level [14][15][16]. In particular Tubbs et al [17] described the presence of smooth muscle, nerve, bone, cartilage and adipose tissue in samples from cadaveric filum externa.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated abundance of collagen and elastic fibres, as well as undifferentiated, progenitor cells or multipotent precursors, explaining, according to some authors, the occurrence of ependymal tumours or teratoma at that level [14][15][16]. In particular Tubbs et al [17] described the presence of smooth muscle, nerve, bone, cartilage and adipose tissue in samples from cadaveric filum externa.…”
Section: Discussionmentioning
confidence: 99%
“…Fontes et al [7] performed an ultrastructural study in the longitudinal and transverse cross sections of the FT in 20 adult cadavers. They showed that the FT was composed of type 1 and 3 collagen bundles on a matrix of elastin and elaunin fibers.…”
Section: Discussionmentioning
confidence: 99%
“…It consists mostly of bundles of collagen fibers and some bundles of neurogenic tissue and is covered by the pia mater, extending from the conus throughout the intradural course. [1][2][3][4] Vascular anatomy of the filum is unique. Its arterial supply is from 1 single longitudinal axis, which is the caudal extension of the radiculomedullary and anterior spinal arteries.…”
mentioning
confidence: 99%